Mosque Library as a Solution to Retract Young Generation's Interest in Reading - Cheris, Rika; Imbardi (FLEKSIBEL: Jurnal Pengabdian Masyarakat, 2022)
In the era of computerization and the ease of using the internet, it reduces interest in reading for most Indonesian people. Moreover, with the covid 19 virus disaster that hit the world, it required the community, especially to learn independently with the internet and the facilities of iphone and smartphone. This will actually further sharpen the decline in the level of intellectualism and intellectuality of the younger generation. Where it has become a provision that reading will add insight and thinking for humans. The current problem is that many students abuse the use of internet media, such as watching shows that can be accessed from the internet that are inappropriate or they can watch pornographic shows. The conditions of online learning and the ease of internet access in the majority of parents and teachers. The presence of a mosque library, is expected to attract the interest of the younger generation. Although this is not the only way to overcome this, efforts to create a library in every mosque, will have a big impact.